Analisis Model Loyalitas Nasabah Tabungan Simpeda Bank Jateng Semarang - Lina, Metha Octo (Jurnal Ilmiah Aset, 2017)
The objective of the research was tested the effect of economic content, relationship commitment, and social content toward trust, satisfaction and customer commitment as well as relationship intention of Bank Jateng branch office Salatiga. The population was debtors of Bank Jateng branch office Salatiga who took its product for business activities. The purposive sampling method was used to determine the samples. The technical analysis applied to test the research hypothesis was Structural Equation Modeling (SEM). The result of the research prevailed that there were positive and significant relationships among economic content and trust, economic content and satisfaction, resource content and trust, resource content and satisfaction, social content and trust, social content and satisfaction, trust and commitment, satisfaction and commitment, and commitment and relationship intention.